HISTORICAL METHOD IN SEARCH STRATEGIES OF UKRAINIAN FASHION HOUSES AND DOMESTIC DESIGNERS’ WORKS OF THE SECOND HALF OF XX CENTURY - Галудзіна-Горобець, В. І. (Art and Design, 2019)
The aim of the article is to identify the peculiarities of the dynamics and figurative and stylistic displays of historical method in the search strategies of Ukrainian Fashion Houses and domestic designers’ works of the second half of XX century. The methodological basis of the article is formed by the principles of the system and synergistic approach, the method of comparative and historical analysis, the method of cultural and historical reconstruction, the historical and biographical method, the analytical and typological method, the art criticism and stylistic analysis. Results. It is established that in the domestic clothes design of the second half of XX century the historical method has developed predominantly in the form of "historical ethno" since the late 1960s. It has been proved that the appeal to the historical theme took place within the Kiev clothes design school and in the exhibition representative costume. It was established that the main sources of design development were the ornamentation of Trypillia, Scythia, Kyiv Rus; traditional folk costumes, motifs of architecture, monumental and decorative and applied arts, folklore, legends; the stylistics of the Ukrainian Baroque, and the main creative methods became stylization, interpretation, association, and quoting. It is proved that the peculiarities of the evolution of historical and national orientation in the works of Ukrainian designers of the second half of XX century was the gradual intensification of ties with the world fashion space, the expansion of the circle of historical national sources, the intertextualization of images, the integration into their structure of the motifs of national architecture and decorative arts, the growth of the associativity of collections and the diversification of methods of design creative work. On the basis of the stylistic analysis of numerous samples of design works it has been demonstrated that the brightest display of historical method in the national clothes design of the second half of XX century became the creative work of L. Avdeyeva and G. Zabashta. The scientific novelty of the article is based on the theoretical and methodological basis and investigation on the empirical material of historical method in the search strategies of the Ukrainian Fashion Houses and domestic designers’ works of the second half of XX century.